Molecular Epidemiology of Carbapenem-Resistant Acinetobacter baumannii Isolates from Northern Africa and the Middle East - Paul G. Higgins; Ralf Matthias Hagen; Bernd Kreikemeyer; Philipp Warnke; Andreas Podbielski; Hagen Frickmann; Ulrike Loderstädt (MDPI AG, 2021)
At the Bundeswehr Hospitals of Hamburg and Westerstede, patients repatriated from subtropical war and crisis zones of Northern Africa and the Middle East were medically treated, including microbiological assessment. Within a six-year interval, 16 Acinetobacter spp. strains, including 14 Acinetobacter baumannii (Ab) isolates with resistance against carbapenems and origins in Afghanistan (n = 4), Iraq (n = 2), Libya (n = 2), and Syria (n = 8) were collected. While clonal relationships of Libyan and Syrian strains had been assessed by superficial next generation sequencing (NGS) and "DiversiLab" repetitive elements sequence-based (rep-)PCR so far, this study provides core genome-based sequence typing and thus more detailed epidemiological information. In detail, sequencing allowed a definitive species identification and comparison with international outbreak-associated Ab strains by core genome multi locus sequence typing (cgMLST) and the identification of MLST lineages, as well as the identification of known resistance genes. The sequence analysis allowed for the confirmation of outbreak-associated clonal clusters among the Syrian and Afghan Ab isolates, indicating likely transmission events. The identified acquired carbapenem resistance genes comprised blaOXA-23, blaOXA-58, blaNDM-1, and blaGES-11, next to other intrinsic and acquired, partly mobile resistance-associated genes. Eleven out of 14 Ab isolates clustered with the previously described international clonal lineages IC1 (4 Afghan strains), IC2 (6 Syrian strains), and IC7 (1 Syrian strain). Identified Pasteur sequence types of the 14 Ab strains comprised ST2 (Syrian), ST25 (Libyan), ST32 (Iraqi), ST81 (Afghan), ST85 (Libyan), and ST1112 (Syrian), respectively. In conclusion, the study revealed a broad spectrum of resistance genes in Ab isolated from war-injured patients from Northern Africa and the Middle East, thereby broadening the scarcely available data on locally abundant clonal lineages and resistance mechanisms.